2021
DOI: 10.1002/jrs.6166
|View full text |Cite
|
Sign up to set email alerts
|

In situ Raman spectroscopy for cultural heritage studies

Abstract: Raman spectroscopy is considered as one of the most appreciated analytical techniques in the cultural heritage research field, thanks to some of its favourable characteristics such as the relatively quick time of analysis, identification of both inorganic and organic molecules. The necessity of conducting the research non-destructively on-site and directly on the artefact brought the technique out of the laboratory. Since 2004, when the first non-commercial mobile Raman instrument for in situ applications on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 170 publications
0
41
0
Order By: Relevance
“…Cultural Heritage was one topic that received the specific attention of Prof. Derek Long at the end of his career. [6,10] The review paper of Rousaki and Vandenabeele (In situ Raman spectroscopy for cultural heritage studies, Gent University, Belgium) [25] points out the many favorable characteristics of the Raman technique in the field of Cultural Heritage studies such as the relatively quick time of analysis and identification of both inorganic and organic molecules, the nondestructive protocol, implemented on-site and directly on the artifact. Since the year 2000, many years of continuous ongoing technical and instrumental developments have passed.…”
Section: Cultural Heritagementioning
confidence: 99%
“…Cultural Heritage was one topic that received the specific attention of Prof. Derek Long at the end of his career. [6,10] The review paper of Rousaki and Vandenabeele (In situ Raman spectroscopy for cultural heritage studies, Gent University, Belgium) [25] points out the many favorable characteristics of the Raman technique in the field of Cultural Heritage studies such as the relatively quick time of analysis and identification of both inorganic and organic molecules, the nondestructive protocol, implemented on-site and directly on the artifact. Since the year 2000, many years of continuous ongoing technical and instrumental developments have passed.…”
Section: Cultural Heritagementioning
confidence: 99%
“…In view of the limitations of Raman spectroscopy, scientists continue to explore and innovate Raman spectroscopy technology [ 12 ]. In recent years, the following advancements have been reported: (1) It is found that metallic or non-metallic nanomaterials and nanostructures can be used as active substrates for Raman spectroscopy to enhance the Raman signal of tested samples; (2) Advanced instruments and methods, including Raman microscopy, cutting-edge enhanced Raman, transverse microradiography, extraction instruments, and stoichiometry methods, have improved the reliability of Raman spectroscopy detection [ 13 ]; (3) The effectiveness of Raman in biomedical imaging and disease diagnosis [ 14 ]; (4) The design and control of ultrafast lasers using nonlinear Raman processes; (5) The application of Raman spectroscopy in art conservation [ 14 ], archaeology [ 15 ], geology [ 16 ], and other emerging fields.…”
Section: Introductionmentioning
confidence: 99%
“…We chose this technique for its significant advantages. First, Raman spectroscopy is nondestructive and noninvasive, making it a safe process for delicate artifacts [18][19][20]. Raman spectroscopy is also very sensitive to a variety of different polymers and can be used to distinguish among them relatively quickly and with great accuracy [6].…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy is also very sensitive to a variety of different polymers and can be used to distinguish among them relatively quickly and with great accuracy [6]. Finally, modern Raman spectrometers provide a portable solution for examining artifacts in situ, making it unnecessary to move artifacts to a laboratory [18][19][20][21]. While using this technique, we do not expect to be able to identify the complete chemical makeup of all the artifacts.…”
Section: Introductionmentioning
confidence: 99%